THE ROLE OF TEAM MANAGEMENT AND ITS RELEVANCE IN THE PROCESS DEVELOPMENT OF PROJECTS - de Paula, Catia Sirlene Martins; Casagrande, Diego José (Revista Interface Tecnológica, 2023)
Management in all sectors is of fundamental importance for the company to develop and grow in an increasingly competitive market. The entire company is involved in projects, which define the paths to be followed for the evolution of the business. Understanding about project team management and its relevance to business growth is a very important factor. The general objective of this study is to highlight the importance of managing the work of the project team. The methodology was Bibliographic Review with consultations in articles and books that discuss the topic objectively. The results show that the leadership and development of teams, if done efficiently, will certainly bring good results for the development of companies. Therefore, extensive knowledge is needed for the management process to truly take place in order to bring growth to both employees and the company in a general context.